2021
DOI: 10.1038/s41598-020-80642-1
|View full text |Cite
|
Sign up to set email alerts
|

Particulate matter emission sources and meteorological parameters combine to shape the airborne bacteria communities in the Ligurian coast, Italy

Abstract: Aim of the present study is to explore how the chemical composition of particulate matter (PM) and meteorological conditions combine in shaping the air microbiome in Savona (Italy), a medium-size, heavily inhabited urban settlement, hosting a wide range of industrial activities. In particular, the air microbiome and PM10 were monitored over six months in 2012. During that time, the air microbiome was highly dynamic, fluctuating between different compositional states, likely resulting from the aerosolization of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 87 publications
1
5
0
Order By: Relevance
“…However, Memarzadeh and Manning ( 2002 ) disagreed with the claim that PM 5 is correlated to microbial counts. In fact, the authors’ finding are similar to Palladino et al ( 2021 ), who performed a scrutinised air quality study and suggested that microbes are present in PM 10. So far, there is no consensus on the exact PM size that is correlated to microbial counts.…”
Section: Resultssupporting
confidence: 85%
“…However, Memarzadeh and Manning ( 2002 ) disagreed with the claim that PM 5 is correlated to microbial counts. In fact, the authors’ finding are similar to Palladino et al ( 2021 ), who performed a scrutinised air quality study and suggested that microbes are present in PM 10. So far, there is no consensus on the exact PM size that is correlated to microbial counts.…”
Section: Resultssupporting
confidence: 85%
“…Airborne bacteria were cultured in Luria Bertani medium for 48 h at 35 °C. The bioaerosol concentration in the air collected by the solid impinger sampler can be calculated using eqn (1).…”
Section: Bioaerosol Sampling and Bacterial Culturementioning
confidence: 99%
“…Bioaerosols are a complex system of dispersed particulate matter in the atmosphere that includes both biotic and abiotic components. 1 Their transmission will cause a variety of disorders, such as infectious diseases, allergies, and acute toxic effects; 2–5 their ambient concentrations in the air are governed by natural and anthropogenic variables, such as geographic location, climate, vegetation cover, and activities. 6,7 With the outbreak of COVID-19 at the end of 2019, national authorities at all levels acted swiftly and took various measures to slow and control the spread of the virus.…”
Section: Introductionmentioning
confidence: 99%
“…In this framework the dispersion model has been applied in the reasonable hypothesis that Legionella is aero-transported in a PM 10 matrix acting as the vector of the infection [54,55]. PM 10 defined as an aerosol suspension composed of particles/droplets with an aerodynamical diameter equal to or less than 10 μm (down to the nm size) is one of the most popular aerosol metrics.…”
Section: Introductionmentioning
confidence: 99%